CHRONOTOPES OF SCREEN CULTURE. DAILY LIFE AS A SCREEN INTERFACE / ХРОНОТОПЫ ЭКРАННОЙ КУЛЬТУРЫ ПОВСЕДНЕВНОСТЬ КАК ЭКРАННЫЙ ИНТЕРФЕЙС - NIKOLAEVA E.V. / НИКОЛАЕВА Е.В. (Наука телевидения)
Mediaportals and screen gadgets isolate a person from reality, turning urban public area into a huge on-screen interface, digital communication transforms the intimate world of smartphone screens into public discourse of displays in public places. But that very screen culture realized man`s dream of Absolute knowledge: now it in any point of space – in the form of visualized information about each individual point and all the space in General.